Research hotspots and trends on acupuncture therapy on vomiting from 1990 to 2022: A bibliometric analysis - Mo-Yao Tan; Chao-Yue Mo; Qian Zhao (Elsevier, 2023)
Objectives: Acupuncture treatment (AT) is commonly utilized for vomiting; however, limited bibliometric analyses exist in this area. Employing a bibliometric approach, we conducted a comprehensive review spanning three decades to assess the research landscape, advancements, and emerging trends in AT for vomiting. Methods: We collected the related literature data from the Web of Science Core Collection (WOSCC) from 1990 to 2022. VOSviewer and R studio were used to perform the bibliometric analysis of AT on vomiting. The status of authors, countries, affiliations, annual publications, keywords, and journals were analyzed accordingly. Results: The earliest relevant paper was published in 1990. Streitberger, K was the most productive author (7 records) and had significant influence (225 reference times, H-Index = 7). The United States had the highest publication count (224 records) and received the most recognition (9719 reference times, H-Index = 52). MEDICINE had the highest number of outputs (34 records), while ANESTHESIA AND ANALGESIA was the most cited journal (1045 reference times). The institution with the most works was Chengdu University of Traditional Chinese Medicine (CDUTCM) (13 records), and the University of California, Los Angeles received the most citations (1252 reference times). Recent and future research hotspots included AT for postoperative vomiting and post-chemotherapy vomiting. Systematic reviews and meta-analyses were the predominant study types. Conclusions: The current status and development prospects of AT for vomiting are shown in this study. In addition, this article provides valuable ideas and potential directions for future research activities.